Past perfect: Letters to Aditi - Anna Varughese (Tanquebar, 2013)
Anna Varughese was only four when she was diagnosed with ulcerative colitis, a serious chronic abdominal disease. From then on, her life was dominated by severe food restrictions, doctors and hospitals. Despite all that, encouraged by her incredibly strong mother, Anna never gave up. She went on to do her MBA, marry her college-mate and best friend TC and have a daughter, Aditi. When Anna was thirty-one, came a grim verdict: her liver was so badly damaged that a transplant was her only hope of survival. By 2002, Anna, who had spent nine months in a small London apartment with her mother, waiting for a donor, had almost given up hope. It was then that Past Perfect took shape. If she couldn t live to tell Aditi the tale, Anna was determined that her daughter would still read her story: that of a wonderful past and an ordinary but lovely life. Here is that captivating story, full of humour and laughter, of a Kerala childhood packed with family, cousins playing never-ending games, gatherings around tables groaning with food and celebrations of weddings, festivals and ordinary days with equal gusto. Anna found her donor in September 2002. Her refusal to let the disease define her or destroy her love for life, will bring hope to anyone faced with a life-threatening condition, and to their families who fight the battle with them.